Ending the Board Game : New Leadership Solutions for Companies - Conger, Jay (Center for Creative Leadership, 2002)
Recent events in corporate America have exposed some failings in the way most companies are led. When the CEO is also the chairman of the board, there is no effective system of checks and balances to ensure not only successful performance but also integrity. However, there are alternatives.